A Clinicoepidemiological Profile of Chronic Wounds in Wound Healing Department in Shanghai. (March 2017) - Sun, Xiaofang; Ni, Pengwen; Wu, Minjie; Huang, Yao; Ye, Junna; Xie, Ting
The aim of the study was to update the clinical database of chronic wounds in order to derive an evidence based understanding of the condition and hence to guide future clinical management in China. A total of 241 patients from January 1, 2011 to April 30, 2016 with chronic wounds of more than 2 weeks' duration were studied in wound healing department in Shanghai. Results revealed that among all the patients the mean age was 52.5 ± 20.2 years (range 2-92 years). The mean initial area of wounds was 30.3 ± 63.0 cm 2 (range 0.25-468 cm 2 ). The mean duration of wounds was 68.5 ± 175.2 months (range 0.5-840 months). The previously reported causes of chronic wounds were traumatic or surgical wounds (n = 82, 34.0%), followed by pressure ulcers (n = 59, 24.5%). To study the effects of age, patients were divided into 2 groups: less than 60 years (<60), and 60 years or older (≥60). The proportion of wounds etiology between the 2 age groups was analyzed, and there was significant statistical difference ( P < .05, 95% confidence interval [CI] = 0.076-0.987). To study the associations between outcome and clinical characteristics in chronic wounds, chi-square test was used. There were significant differences in the factor of wound infection. ( P = .035, 95% CI = 0.031-0.038) Regarding therapies, 72.6% (n = 175) of the patients were treated with negative pressure wound therapy. Among all the patients, 29.9% (n = 72) of them were completely healed when discharged while 62.7% (n = 150) of them improved. The mean treatment cost was 12055.4 ± 9206.3 Chinese Yuan (range 891-63626 Chinese Yuan). In conclusion, traumatic or surgical wounds have recently become the leading cause of chronic wounds in Shanghai, China. Etiology of the 2 age groups was different. Infection could significantly influence the wound outcome.